Brand Identity Transfer and Consumers Sport Commitment in the Iranian Football Premier League: Mediating Role of Promotional and Advertising Tools - Ehsan Asadollahi; Mohammad Keshtidar; Reza Heydari; Marko Peric (Journal of New Studies in Sport Management, 2020)
Sports advertising is one of the methods used by most companies to introduce their brands and products and expand their market. This study aimed to investigate the relationship between brand identity transfer and sport commitment with the mediating role of promotional and advertising tools from the perspective of sports consumers in Iran. 500 sports consumers participated in this study and completed the research questionnaire. The results of the structural equation modeling (SEM) indicate that there is a significant relationship between brand identity transfer and sport commitment and their dimensions, with the mediating role of promotional and advertising tools. Further, TV, mobile and social networks should have a priority over other promotional tools when transferring brand identity and sports commitment of consumers. Besides, contributing to the advancement of theory, this study has important practical implications for sport marketers and managers who are searching effective promotional and advertising tools to re-engage existing consumers or to acquire new ones.